2023
DOI: 10.3389/fpsyg.2022.1031902
|View full text |Cite
|
Sign up to set email alerts
|

What factors affect team members’ evaluation of collaboration in medical teams?

Abstract: IntroductionPerceived teamwork quality is associated with numerous work-related outcomes, ranging from team effectiveness to job satisfaction. This study explored what situational and stable factors affect the perceived quality of teamwork during a specific team task: when a medical team comprising a senior (supervisor) and a junior (trainee) physician diagnoses a patient.MethodsDuring a field study in an emergency department, multisource data describing the patients, the diagnosing physicians, and the context… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Knowing what the participants meant to understand better through collaborative dynamics would be interesting. Although many authors indicated the quality of inter-professional collaboration as a main factor influencing JS, the environmental perception of collaborative quality may vary among individuals and professional profiles [ 78 ]. Staff nurses involved in the care process were led by various figures (e.g., head nurse, senior nurse, nurse director) with different leadership styles, depending on their education and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing what the participants meant to understand better through collaborative dynamics would be interesting. Although many authors indicated the quality of inter-professional collaboration as a main factor influencing JS, the environmental perception of collaborative quality may vary among individuals and professional profiles [ 78 ]. Staff nurses involved in the care process were led by various figures (e.g., head nurse, senior nurse, nurse director) with different leadership styles, depending on their education and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Team members' perceptions and attitudes concerning teamwork are linked to patient safety and quality care (Manser, 2009;Müller et al, 2018;Kämmer et al, 2023), summarizing that the perceived teamwork quality differs depending on the profession, status, experience, or hierarchical position (Kämmer et al, 2023). Therefore, the subjective, self-perception analysis furnishes insights into social teamwork interactions, training activities, and outputs (such as patient safety risks and team performance perception) of it.…”
mentioning
confidence: 99%